Formação de Professores e o uso significativo de computadores na Prática Pedagógica - Garcia, Fernando (2005)
The present work concerns the recognition of how important it is to incorporate New Technologies of Communication and Information, especially the computer, in school education. Highlighting the relevance of teachers education toward that objective, the purpose of the research was to indicate possible recommendations for teachers education to get a significant use of those technologies. The aspect to be studied privileged the meanings of the use of new technologies and how the teachers have developed them. In order to recognize such meanings, seen as important references to teachers education, a research was conducted in two schools, involving two groups of teachers. That research aimed to understand how the teachers get along with new technologies, how significant it is to use the computer laboratory for the researched schools, how important the laboratory is for the students education and how education might contemplate the use of new technologies. The data were analyzed through questionnaires and interviews with the teachers, coordinators and principals of both schools. The collected data show that regarding the teachers education and the teachers individual experience, there is a construction of meanings that imply the use of the computer as something esthetic , just to complete the pedagogical process. Although the process does overcome the resistance to the use of that tool, it still does not fully exploit the possibilities of technological resources in order that they can be included in teaching situations to offer real chances of learning